Geocoding and Social Marketing in Alabama's Cancer Prevention Programs - Julianna W. Miner, MPH; Arica White, MPH; Anne E. Lubenow, MPH; Sally Palmer (Centers for Disease Control and Prevention, 2005)
The Alabama Department of Public Health (ADPH) is collaborating with the National Cancer Institute to develop detailed profiles of underserved Alabama communities most at risk for cancer. These profiles will be combined with geocoded data to create a pilot project, Cancer Prevention for Alabama's Underserved Populations: A Focused Approach. The project's objectives are to provide the ADPH's cancer prevention programs with a more accurate and cost-effective means of planning, implementing, and evaluating its prevention activities in an outcomes-oriented and population-appropriate manner. The project links geocoded data from the Alabama Statewide Cancer Registry with profiles generated by the National Cancer Institute's cancer profiling system, Consumer Health Profiles. These profiles have been successfully applied to market-focused cancer prevention messages across the United States. The ADPH and the National Cancer Institute will evaluate the efficacy of using geocoded data and lifestyle segmentation information in strategy development and program implementation. Alabama is the first state in the nation not only to link geocoded cancer registry data with lifestyle segmentation data but also to use the National Cancer Institute's profiles and methodology in combination with actual state data.